Polymer-coated hexagonal upconverting nanoparticles: chemical stability and cytotoxicity - Patsula, Vitalii; Mareková, Dana; Jendelová, Pavla; Nahorniak, Mykhailo; Shapoval, Oleksandr; Matouš, Petr; Oleksa, Viktoriia; Konefał, Rafał; Vosmanská, Magda; Machová-Urdziková, Lucia; Horák, Daniel (Frontiers in Chemistry, 2023)
Large (120 nm) hexagonal NaYF4:Yb,Er nanoparticles (UCNPs) were synthesized by hightemperature coprecipitation method and coated with poly(ethylene glycol)-alendronate (PEG-Ale), poly(N,N-dimethylacrylamide-co-2-aminoethylacrylamide)-alendronate (PDMA-Ale) or poly(methyl vinyl ether-co-maleic acid) (PMVEMA). The colloidal stability of polymer-coated UCNPs in water, PBS and DMEM medium was investigated by dynamic light scattering; UCNP@PMVEMA particles showed the best stability in PBS. Dissolution of the particles in water, PBS, DMEM and artificial lysosomal fluid (ALF) determined by potentiometric measurements showed that all particles were relatively chemically stable in DMEM.